2009
DOI: 10.1016/j.atherosclerosis.2008.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory fitness and coronary artery calcification in young adults: The CARDIA Study

Abstract: Whether cardiorespiratory fitness relates to early subclinical atherosclerotic vascular disease remains unknown. We investigated the relation of cardiorespiratory fitness to coronary artery calcification (CAC) in 2373 African-American and White young adults from the Coronary Artery Risk Development in Young Adults (CARDIA) Study. We measured cardiorespiratory fitness in 1985-1986 (baseline) using a symptom-limited exercise test on a treadmill. Coronary calcium scores were measured in 2001-2002 (year 15) using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 44 publications
2
33
0
1
Order By: Relevance
“…Furthermore, several prior studies have reported that cardiorespiratory fitness measured by treadmill test is inversely associated with CAC prevalence [57,58]. Nevertheless, whether there is a significant interaction between exercise capacity and CACS influencing adverse outcomes remains unclear.…”
Section: Combined Effects Of Exercise Capacity and Cacs On Acmmentioning
confidence: 99%
“…Furthermore, several prior studies have reported that cardiorespiratory fitness measured by treadmill test is inversely associated with CAC prevalence [57,58]. Nevertheless, whether there is a significant interaction between exercise capacity and CACS influencing adverse outcomes remains unclear.…”
Section: Combined Effects Of Exercise Capacity and Cacs On Acmmentioning
confidence: 99%
“…The CARDIA study showed that physical fitness measured at baseline was inversely associated with early atherosclerotic vascular disease in young adults. High-fitness young adults (treadmill time: men ≥13.5 min, women ≥10 min; age 18-30 years) had a 41% lower risk of having CAC as compared with low-fitness counterparts (treadmill time: men <11 min, women <7.3 min) over 15 years [31]. One cross-sectional study showed a null association between physical fitness, as assessed by continuous metabolic equivalents (MET; 1 MET = 3.5 ml O 2 /kg/min), and CAC in US women aged 40-90 years [32].…”
Section: Physical Activity or Physical Fitness And Cacmentioning
confidence: 99%
“…Interestingly, several population-based studies indicate no association between physical activity and CAC. The Multi-Ethnic Study of Atherosclerosis (MESA) and the CARDIA study have shown that physical activity was not associated with CAC [31,33]. This may be due to the inaccurate measurement of physical activity in both cross-sectional and observational studies.…”
Section: Physical Activity or Physical Fitness And Cacmentioning
confidence: 99%
“…Among the 2,373 African-American and white young adults enrolled in the Coronary Artery Risk Development in Young Adults Study, baseline cardio-respiratory fitness was inversely related with the development of CAC during the subsequent 15 years of follow-up. Nonetheless, whether the main determinant of CAC deposition is the genetic background or PA of study subjects could not be addressed in the study [34]. …”
Section: Pa and Markers Of Subclinical Atherosclerosis In The Generalmentioning
confidence: 99%